2013
DOI: 10.1074/jbc.m113.515510
|View full text |Cite
|
Sign up to set email alerts
|

Motor Domain Phosphorylation Modulates Kinesin-1 Transport

Abstract: Background: Kinesin-1 motor domain phosphorylation has been linked to impaired transport in axons. Results: A mechanism by which phosphorylation could affect transport is proposed. Conclusion: Phosphorylation decreases the stall force of kinesin and stabilizes autoinhibition. Significance: Kinesin phosphorylation could be used to fine tune the direction of cargo transport and contribute to pathology in neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…Mutant huntingtin induces the aberrant activation of neuronal-specific JNK3, a kinase that can phosphorylate KIF5C at S176 in vitro [57, 58]. Studies on phosphomutants (at the conserved KIF5B S175 site) indicate that while ATPase activity, microtubule-binding, and processivity are not altered, there is some enhanced autoinhibition of the phosphorylated kinesin motor that may favor minus-end-directed over plus-end-directed motility [59]. Thus, direct phosphorylation of molecular motors may also contribute to the tuning of transport, and this tuning may be altered in disease.…”
Section: Scaffolding Proteins Coordinate Motor Activitymentioning
confidence: 99%
“…Mutant huntingtin induces the aberrant activation of neuronal-specific JNK3, a kinase that can phosphorylate KIF5C at S176 in vitro [57, 58]. Studies on phosphomutants (at the conserved KIF5B S175 site) indicate that while ATPase activity, microtubule-binding, and processivity are not altered, there is some enhanced autoinhibition of the phosphorylated kinesin motor that may favor minus-end-directed over plus-end-directed motility [59]. Thus, direct phosphorylation of molecular motors may also contribute to the tuning of transport, and this tuning may be altered in disease.…”
Section: Scaffolding Proteins Coordinate Motor Activitymentioning
confidence: 99%
“…These assays have strongly demonstrated that pairs of motors (kinesin and mammalian dynein 12a , 12c , 13 or kinesin and yeast dynein) 11 undergo a tug-of-war in vitro without external signals or cofactors. In addition, when cofactors are examined in vitro with a motor (e.g.…”
Section: Controlling the Transport Complex From The Bottom Upmentioning
confidence: 99%
“…12a , 13,23b In experiments by Muresan et al, using latex beads coated with kinesin and dynein, the beads always walked in the kinesin direction, i.e. bidirectional motility was not observed.…”
Section: Controlling the Transport Complex From The Bottom Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Because motor behaviour can be altered by phosphorylation (Hirokawa et al, 2009;DeBerg et al, 2013), Halo might control the phosphorylation state of kinesin-1 and, thus, its interaction with the switching mechanism. If Halo is counteracted by a ubiquitous kinase, then it would only be effective if present in high enough concentrations to outperform the kinase, possibly explaining both the threshold effect and the quick reversal of transport once Halo levels drop.…”
Section: The Mechanism Of Halo Actionmentioning
confidence: 99%